FENOMENA SEXUAL HARASSMENT PADA WANITA PEKERJA DI KOTA MAKASSAR - Dyan Fauziah Suryadi; Rohani Rohani (AkMen JURNAL ILMIAH, 2019)
This study aims to describe the phenomenon of sexual harassment in working women in the city of Makassar. This study involved ten adult women who had experienced sexual harassment. Subjects are selected based on several criteria, namely women who are in adulthood and are employees of a company. This research is qualitative in that it explores and understands the meanings which by a number of individuals or groups of people are ascribed to social or humanitarian problems. The design of this research is phonology that aims to understand one's life experiences, how an event has an impact on his daily life. Data is collected by conducting depth interviews with the subject and several significant people to fulfill the required information. The results of the study showed that the sexual harassment experienced by victims was in the form of touch and verbally carried out by superiors and coworkers with the frequency of events more than once. In general, victims feel angry, irritated, sad, scared, worried, and ashamed. The behavior displayed by the victim by allowing recurring events, moving branches, resigning, avoiding the perpetrators and activities involving the perpetrators, and reprimanding and scolding the perpetrators during the incident. Sexual harassment causes three people to experience severe stress, four people experience moderate stress, two people experience mild stress, and one person does not experience stress. In addition to experiencing stress, some victims also experienced a decline in work performance.